Study of consumer behavior in otc drug market - V V Dorofeeva; G A Galkina; C V Sudarenko (RUDN Journal of Medicine, 2013)
The article is devoted to research of consumer behavior in the pharmaceutical market. Authors scientifically proved approaches to its investigation according to peculiarities of formation of OTC (OTC — Over The Counter) market. A method of determination of consumer satisfaction is presented and parameters of drugstore activity needing adjustment are revealed. According to loyalty target consumer segments are allocated, for each of which loyalty determinants are defined. The technique of possible development of OTC consumer behavior based on the consumer’s group requirements is offered.